PERSPEKTIF RANTAI PASAR BAWANG MERAH DI KABUPATEN BREBES, JAWA TENGAH - Darwis, Valeriana; Mayrowani, Henny (Lampung University)
<!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> perspective, shallotTrade liberalisation creates the opportunity and challenge in the development of horticultural product. Trading will give an incentive for the farmers to increase their production in term of quantity and quality, and market is important to distribute the product.Â Shallot is one of the important horticultural product in Indonesia. Kabupaten Brebes is one of the famous production center of shallot, and the farmers still haveÂ a difficulty to sell their product. Itâs mean that the bargaining power of the farmers are still weak, marketing channel is too long, shallot price are fluctuated and unpredictable, so the farmers are not enough to get benefit from market margin yet. Availability of imported shallot in the local market caused more serious problems in the marketing of farmers product.Â It is too difficult to get a high price for their product. Shortening the marketing channel is one of the effort to make a marketing efficiency. In the last decade, there was a change of the farmers behaviour in selling product.Â Ten years ago, one hundred percent of farmers sell the product to the village collector.Â By infrastructure development, itâs decrease to 75% of farmers whose were selling the product to the village collector and the rest directly sell to wholesaler in the town.Â It is suggested that local government must more develop the local infrastructure and create an import regulation especially on time and tax of shallot import in order to increase the farmers incomes.